Riko the series (murrotal edition): Surah At-Tin episode as a medium to introduce surah At-Tin to children - Fatimah Azzahro; Hartini Salama (Mitra Palupi, 2022)
Background: Quran's introduction to children has evolved over time. Animation can now be a medium to learn the Quran such as